Dinamika Putusan Pengadilan dalam Penyelesaian Sengketa Kewarisan - Rahman, Ahmad Haikal (Lembaga Yasin AlSys, 2023)
This content departs from the rise of inheritance disputes in cases at courts in Indonesia. The property left by someone who dies often creates family divisions, starting from who is entitled to the inheritance to how much part an heir gets from the inheritance. This dispute occurs because the heirs are dissatisfied with what he gets from the heir or feel more entitled to own the inherited property because the Islamic legal system uses a 2:1 system which does not seem to give justice to another. Inheritance disputes that occur usually are related to heirs, heir and Inheritance. This paper aims to show several types of disputes that occur, especially those that are brought to court and to see how the dynamics and ways of judges in making decisions on these cases so that they become a picture of the future for other judges in dealing with inheritance dispute cases in particular.